Ngerambat Gending: A Composition of Essential Idea of Karawitans Definition | Ngerambat Gending: Sebuah Komposisi dari Ide Esensi Definisi Karawitan - Pande Kadek Ega Sasdicka; I Nyoman Kariasa (Pusat Penerbitan LPPMPP ISI Denpasar, 2021)
There is still a gap of vocal use separators in various Balinese karawitan compositions that develop lately, such as; Sandya gita, Gegitaan and Gegerongan. Karawitan composition